(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
It is generally agreed that games, encourage learners to interact, cooperate, to be creative and spontaneous in using the language in a meaningful way. Learners want to take part in activities, to play games and are generally quite competitive. In order for them to take part they must be able to understand and communicate in the target language. Moreover, games also encourage learners to keep interested in the work and a teacher can use them to create contexts in which the language is useful.